2009
DOI: 10.1128/jvi.02546-08
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Teleost Fish Retroviruses: Characterization of New Retroviruses with Cellular Genes

Abstract: The interactions between retroviruses and their hosts can be of a beneficial or detrimental nature. Some endogenous retroviruses are involved in development, while others cause disease. The Genome Parsing Suite (GPS) is a software tool to track and trace all Retroid agents in any sequenced genome (M. A. McClure et al., Genomics 85:512-523, 2005). Using the GPS, the retroviral content was assessed in four model teleost fish. Eleven new species of fish retroviruses are identified and characterized. The reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…NA viruses and a subset of retroviruses are known to encode homologs of host cell enzymes involved in nucleotide metabolism (e.g., thymidine kinase [TK], ribonucleotide reductase, uracil-DNA glycosylase, and/or dUTPase), which are mostly not essential for viral replication in cell cultures (1)(2)(3)(4)(5)(6)(7). Of these, viral dUTPase (vdUTPase) is of special interest because it is the homolog most widely encoded by viruses (3,(7)(8)(9).…”
mentioning
confidence: 99%
“…NA viruses and a subset of retroviruses are known to encode homologs of host cell enzymes involved in nucleotide metabolism (e.g., thymidine kinase [TK], ribonucleotide reductase, uracil-DNA glycosylase, and/or dUTPase), which are mostly not essential for viral replication in cell cultures (1)(2)(3)(4)(5)(6)(7). Of these, viral dUTPase (vdUTPase) is of special interest because it is the homolog most widely encoded by viruses (3,(7)(8)(9).…”
mentioning
confidence: 99%
“…Retroviruses are most commonly analyzed according to phylogenetic relationships of the highly conserved reverse transcriptase (RT) region of pol (7)(8)(9)(10)(11), rather than env. In phylogenetic analyses of the RT region, ERVs cluster into three broad classes that include the known exogenous retroviruses: class I includes gamma-and epsilonretroviruses; class II, beta-, delta-, and alpharetroviruses and lentiviruses; and class III, spumaretroviruses (10).…”
mentioning
confidence: 99%
“…Genetic analysis has shown that fish retroviruses are a highly diverse group compared to other retroviruses (Basta et al 2009). Some of the fish retroviruses exhibit unique features, such as those associated with skin tumors in walleyes which encode cyclin homologs.…”
Section: Discussionmentioning
confidence: 99%
“…All genetic elements that contain a gene encoding reverse transcriptase (RT) are referred to as retroelements or retroids (Hull 2001, Basta et al 2009). According to the classification proposed by Hull (2001) retroelements comprise two major groups, Retrovirales which consist viral elements and Retrales containing non-viral elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation